Microfinance at the margin: Experimental evidence from Bosnia and Herzegovina - Britta Augsburg; Ralph de Haas; Heike Harmgart; Costas Meghir (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
We use a randomised controlled trial (RCT) to analyse the impact of microcredit on poverty reduction in Bosnia and Herzegovina. The study population are loan appli-cants that would normally have just been rejected based on regular screening. We find that access to credit allowed borrowers to start and expand small-scale busi-nesses. Households that already had a business and where the borrower had more education, ran down their savings, presumably to complement the loan and to achieve the minimum amount necessary to expand their business. In less-educated households, however, consumption went down. A key new result is that there was a substantial increase in the labour supply of young adults (16-19 year olds). This was accompanied by a reduction in school attendance.
Keywords: O16; G21; D21; I32; 330; microfinance; liquidity constraints; human capital; randomised controlled trial